Pengaruh Korosi Terhadap Kegagalan Logam pada Jembatan : Literature Review - Anita Putri Kurniasari; Yasmina Amalia (Politeknik Negeri Jakarta, 2022)
Steel bridges are used as construction materials because of their lightweight properties, durabil-ity, and ease for assembled. But failure on steel bridges increases exponentially. Structural fa-tigue, material aging combined with an increase in traffic loads, is a cause in damage to the bridge, where in this case corrosion is the main discussion of decreased quality and failure on the bridge. In the results of the literature review of several papers, the results were obtained that from visual observations in bridge steel in the sea water environment, rivers, and in the envi-ronment around the toilet waste. Damage to the bridge structure caused by corrosion from chlo-ride ions in sea water is higher than corrosion in the river environment and waste fluids on the train. The corrosion rate that occurs in the marine environment is higher than the river environ-ment and toilet waste fluids. In the corrosive environment, chloride ions or sulfate will diffuse into steel through concrete bridge structure.